2021
DOI: 10.4314/tjpr.v18i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of active saponins from Panax ginseng Meyer

Abstract: Purpose: To investigate the pharmacological effects of the active saponins isolated from Panax ginseng Meyer (P. ginseng) via extraction, heat treatment, and enzyme conversion. Methods: The effects of active saponins on rat blood were determined using a multichannel analyzer. The population doubling time (PDT) of mesenchymal stem cells (MSCs) and human-derived leukocyte cancer cells (A549) was determined by cell counting. b-galactosidase was measured in human toothderived stem cells (HTS) using a β-galac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that Rg2 and Rh1 have erythrocyte protective effects, but no reports on compound K have been reported. 25 The compound K concentration was based on 20 nM, referring to a previous study by Bae et al 22 A comparison of the packed blood sample with compound K and non-treatment groups showed that the half-life was 30 days in the untreated group, but the half-life extended to 45 days in the treated group (data not shown). A microscopic examination of the erythrocyte morphology revealed that the compound K group significantly reduced the occurrence of debris and aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Rg2 and Rh1 have erythrocyte protective effects, but no reports on compound K have been reported. 25 The compound K concentration was based on 20 nM, referring to a previous study by Bae et al 22 A comparison of the packed blood sample with compound K and non-treatment groups showed that the half-life was 30 days in the untreated group, but the half-life extended to 45 days in the treated group (data not shown). A microscopic examination of the erythrocyte morphology revealed that the compound K group significantly reduced the occurrence of debris and aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Compound K was treated at a final concentration of 20 nM, as previously described. 22 To compare the erythrocyte half-life span, a CBC analyzer was used. The control (30 days, from 5.07 to 1.94 × 10 6 cells/μL), compound K (30 days, from 5.39 to 4.1 × 10 6 cells/μL), and the compound K-treated blood groups had an erythrocyte half-life-span of 15 days longer.…”
Section: Complete Blood Cell Counts Of Stored Blood With Compound K A...mentioning
confidence: 99%
“…D/DA ethanol solution was firstly mixed with the DPPH stock solution in methanol for DPPH radical scavenging activity. The final concentration was 0.2 mM for DPPH in every D/DA (1,10,20,40,80, and 160 µg/mL) ethanol solution (experiment), 0.2 mM DPPH in ethanol (Control), and D/DA in a methanol and ethanol solutions (blank). The standard solution used was αtocopherol.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…Angelica gigas Nakai is a medicinal herb that is widely used in Asia (Korea, Japan, and China) [1]. In the US and Europe, AGN is used as a dietary supplement [2].…”
Section: Introductionmentioning
confidence: 99%